2021
DOI: 10.1002/elan.202100261
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Electrochemical Determination of Paracetamol and Allura Red in Pharmaceutical Doses and Food Using a Mo(VI) Oxide‐Carbon Paste Microcomposite

Abstract: This work presents a new application for MoO 3 combined with carbon paste to prepare a microcomposite electrode (Mo(VI) Ox /CPE) for the simultaneous determination of paracetamol (PCM) and Allure Red (AR) by square-wave voltammetry (SWV). The anodic peak currents for PCM and AR were 70.0 and 80.0 % high compared with an unmodified carbon paste electrode.The surface areas of Mo(VI) Ox /CPE and CPE were evaluated by cyclic voltammetry. The detection limit were 0.14 and 0.38 μmol/L for PCM and AR respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…On the other hand, for the electrode modified with graphene and chitosan, the value obtained was slightly lower than that in a previous report, which was 0.16 cm 2 [ 40 ]. Moreover, these results are very similar to previous reports on the use of electrodes with metal oxides and metal nanoparticles [ 44 , 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, for the electrode modified with graphene and chitosan, the value obtained was slightly lower than that in a previous report, which was 0.16 cm 2 [ 40 ]. Moreover, these results are very similar to previous reports on the use of electrodes with metal oxides and metal nanoparticles [ 44 , 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
“…In the three electrodes, it was clearly observed that anodic peak currents increased proportionally with an increasing scan rate of between 0.02 and 0.10 V/s, but there was a slight increase with Ch-G/GCE. The linear relation for the anode and cathode currents (I pa and I pc ) versus the scan rate (ʋ)½ was plotted for the three electrodes, and the values of the slopes were substituted into the Randles–Sevcik equation [ 40 , 44 ]: I p = 2.69 × 10 5 n 3/2 AD 1/2 ν ½ C to obtain the value of the active surface area in cm 2 , where I p is the anodic peak current, n is the number of electrons ( n = 1), D is the diffusion coefficient for K 4 Fe(CN) 6 (7.6 × 10 −6 cm 2 s −1 ), ν 1/2 is the scan rate, and C is the ferricyanide concentration in mol/cm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Normally, AR can be oxidized in a wide range of acidic pH values between 2.0 and 7.0 [18,23] . In this case, the study of AR activity as a function of pH using phosphate buffer solution (PBS) values between 2.0 and 6.0 (Figure 4A) showed that the highest anodic peak current was at pH 2.0.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, carbon electrodes are the most used for the development of modified electrodes, in some cases they have been used with Ca‐doped ZnO for detection of antihistamine drug, [40] Carbendazim [41] and Trimethoprim [42] and Silver‐Doped Titania for Furantril [43] . Cyclic voltammetry is a very versatile tool to study and characterize the properties of an electrode such as mass transport and active area [18,21,17] . These reports are clear evidence of the utility of carbon electrodes as an essential raw material in the development of electrochemical sensors [44–47] …”
Section: Introductionmentioning
confidence: 99%
“…Voltammetry is electrochemical method of analysis, and has recently been increasingly used to develop new, fast, cheap, and selective sensors. [11] Over the past ten years, the literature has described a large number of voltammetric sensors developed for various purposes, in particular, for the analysis of pharmaceuticals, [12][13][14] natural antioxidants [15,16] and food dyes. [17][18][19] Thus, a number of sensors modified with metal nanoparticles, [20][21][22] surfactants, [19,23] carbon nanomaterials, [24][25][26][27] ionic liquids [28][29][30] and others have been described to determination of Allura Red AC.…”
Section: Introductionmentioning
confidence: 99%